TREN RISET PEMANFAATAN LEARNING ANALYTICS PADA DESAIN PEMBELAJARAN MODEL ADDIE: ANALISIS BIBLIOMETRIK (2015–2025) - Luthfi Yacob; Yunita Septiani; Adam Panca Putra Pinaria; Dirgantara Wicaksono (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT The ADDIE (Analysis, Design, Development, Implementation, Evaluation) model remains one of the most widely adopted instructional design frameworks; however, its linear approach is often considered insufficiently responsive to the demands of data-driven learning in the digital era. This study aimed to map publication trends, intellectual structure, thematic clusters, and the contribution of learning analytics across the ADDIE phases during the 2015–2025 period. A bibliometric approach was employed using data retrieved through Publish or Perish from the Scopus and Google Scholar databases. Literature selection followed the PRISMA protocol, resulting in 55 eligible documents from an initial dataset of 310 records. Data were analyzed using Biblioshiny to evaluate publication performance and VOSviewer to map keyword co-occurrence. The findings revealed a compound annual growth rate of 23.11%, indicating a substantial increase in research output, although the thematic collaboration network remained sparse and no dominant core author group was identified. Four thematic clusters were identified, with learning analytics and instructional design serving as bridging nodes across the research landscape. The contribution of learning analytics to the ADDIE phases was uneven, with the Design and Development phases receiving the greatest attention, whereas the Analysis phase—the foundation of the instructional design process—received the least attention. The study concludes that the integration of learning analytics into the ADDIE model remains asymmetric, highlighting the need for greater research emphasis and practical implementation, particularly in the Analysis phase, to support more evidence-based instructional decision-making. ABSTRAK Model ADDIE (Analysis, Design, Development, Implementation, Evaluation) merupakan salah satu kerangka desain instruksional yang masih banyak digunakan, namun pendekatan yang bersifat linier dinilai kurang adaptif terhadap kebutuhan pembelajaran berbasis data pada era digital. Penelitian ini bertujuan memetakan perkembangan publikasi, struktur intelektual, klaster tematik, serta kontribusi learning analytics pada setiap fase ADDIE selama periode 2015–2025. Penelitian menggunakan pendekatan bibliometrik dengan data yang diperoleh melalui Publish or Perish dari basis data Scopus dan Google Scholar. Seleksi literatur dilakukan mengikuti protokol PRISMA sehingga diperoleh 55 dokumen yang memenuhi kriteria inklusi dari 310 dokumen awal. Analisis dilakukan menggunakan Biblioshiny untuk mengevaluasi performa publikasi dan VOSviewer untuk memetakan keterkaitan kata kunci. Hasil penelitian menunjukkan pertumbuhan publikasi yang meningkat dengan laju pertumbuhan majemuk tahunan sebesar 23,11%, namun kepadatan jaringan kolaborasi tematik masih rendah dan belum terbentuk kelompok penulis inti yang dominan. Analisis menghasilkan empat klaster tematik, dengan learning analytics dan instructional design berperan sebagai penghubung antarklaster. Kontribusi learning analytics terhadap fase ADDIE masih belum merata, didominasi pada fase Design dan Development, sedangkan fase Analysis memperoleh perhatian paling rendah meskipun menjadi fondasi utama proses desain pembelajaran. Penelitian ini menyimpulkan bahwa integrasi learning analytics dalam model ADDIE masih bersifat asimetris sehingga diperlukan penguatan penelitian dan implementasi, terutama pada fase Analysis, untuk mendukung pengambilan keputusan instruksional yang lebih berbasis bukti.